Argentinian unhatched pterosaur fossil - Chiappe, Luis (2004)
Our knowledge of the eggs and embryos of pterosaurs, the Mesozoic flying reptiles, is sparse. Until now, the recent discovery of an ornithocheirid embryo from 121-million-year-old rocks in China1 constituted the only reliable evidence of an unhatched pterosaur. Here we describe an embryonic fossil of a different pterosaur from the Early Cretaceous lacustrine deposits of Loma del Pterodaustro (the Lagarcito Formation, which is about 100 million years old) in central Argentina. This new fossil provides insight into the eggshell morphology, early growth and nesting environments of pterosaurs.